THE IMPLEMENTATION OF APTITUDE TREATMENT INTERACTION (ATI) MODEL TO IMPROVE ENGLISH GRAMMAR MASTERY - Sudharmono, Sudharmono; Ali, Sayyidina (Fakultas Keguruan dan Ilmu Pendidikan, 2016)
A good learning approach is required in teaching to help the students in increasing their achievement. The aims of this research is to investigate the effects of aptitude treatment interaction (ATI) model in improving the students’ achievement in teaching English grammar. This study was pre-experimental model consisting of one group. The study was conducted at SMA Negeri 1 Bontolempangan, Gowa South-Sulawesi. Samples of the study were 30 students by using purposive sampling technique. The data were collected with pre-test, treatment, and post-test. The pretest and posttest were administered which consisted of multiple choice form. The comparison between the students’ score improvement from pretest to posttest demonstrated a significant difference. The research found that the result on pre-test mean score was 4.65, and the result on post-test mean score was 7.11. The data was analyzed by using t-test; the result of t-test (17.57) was greater than the t-table (2.045). It indicated that the alternative hypothesis (H1) was accepted and the (H0) was rejected. Based on the result of data analysis, the researcher concluded that the implementation of Aptitude Treatment Interaction (ATI) model in teaching grammar can increase the students’ achievement.